2012
DOI: 10.17795/jjnpp-3588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Green Tea Extract on Mouth Bacterial Activity in the Presence of Propylene Glycol

Abstract: Background: Compounds present in green tea have proved to inhibit the growth and activity of bacteria associated with infections. Objectives: To assess the effects of green tea leaves extract in presence of propylene glycol on the aerobic mouth bacteria load. Materials and Methods: Saliva of 25 volunteer girl students aging 20-25 years were selected and evaluated by a mouthwash sample containing 1% tannin, as the most effective antibacterial complex in green tea. Comparative studies were also conducted between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Tea catechins possess galloyl radicals that could restrain collagenase enzymes present in eukaryotic and prokaryotic cells, responsible for the disruption of collagen in gingival tissues in patients suffering from periodontal disease. Catechin also reduces the protease enzyme of P. gingivalis , thus reducing the damage to the periodontal tissues 26,27 . Catechins in Green tea hinder tyrosine phosphatase protein in the bacteria Prevotella intermedia responsible for gingival and periodontal diseases 41 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tea catechins possess galloyl radicals that could restrain collagenase enzymes present in eukaryotic and prokaryotic cells, responsible for the disruption of collagen in gingival tissues in patients suffering from periodontal disease. Catechin also reduces the protease enzyme of P. gingivalis , thus reducing the damage to the periodontal tissues 26,27 . Catechins in Green tea hinder tyrosine phosphatase protein in the bacteria Prevotella intermedia responsible for gingival and periodontal diseases 41 …”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have observed a reduction in the gingival index when using green tea mouthwash, showing a therapeutic effect that improves the gingival status of patients 26 . A recent systematic review evaluated the usefulness of green tea and chlorhexidine mouthwash as an anti‐plaque agent and showed that green tea mouthwash comparably reduces plaque and gingival index 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Moghbel et al ., using a sample with 1% tannin compared to 0.25% and 0.5% could decrease the microbial load in the saliva samples as much as twofold (26–32%), and even more with the addition of propylene glycol; therefore, in the present study, we used a 1% tannin preparation of green tea …”
Section: Discussionmentioning
confidence: 99%
“…According to Moghbel et al, using a sample with 1% tannin compared to 0.25% and 0.5% could decrease the microbial load in the saliva samples as much as twofold (26-32%), and even more with the addition of propylene glycol; therefore, in the present study, we used a 1% tannin preparation of green tea. 24,31,32 Chlorhexidine is known as the most effective antiplaque agent to date. In their systematic review, Berchier et al stated that while 0.2% and 0.12% concentrations of chlorhexidine have the same efficacy on gingivitis, the 0.2% concentration better inhibits plaque accumulation.…”
Section: Discussionmentioning
confidence: 99%